Scholastic Rationales of 'Conscience', Early Modern Crises of Credibility, and the Scientific-Technocultural Revolutions of the 17th and 20th Centuries - Nelson, Benjamin (Journal for the scientific study of religion, 1968)
Our galloping 20th Century Revolutions of Science and Technoculture have deep roots in the Protestant Reformations and the Revolutions in Science and Philosophy of the 16th and 17th Centuries. These decisive recastings of the relations of conscience--moral, religious, scientific--and character need to be seen in wider frames than those adopted by Max Weber in his renowned "Protestant Ethic and the Spirit of Capitalism" (1904-05). To do justice to these developments, we have to go beyond Weber in the spirit of his last essays before his death in 1920. New stress has to be given to the role of the revolutions of organized systems of "rationales" both of action and thought within the processes Weber described under the heading of "Rationalizations." The breakthroughs to the modern world and the propulsive developments now in progress have less to do with the "spirit of capitalism" and the "profit motive" in their narrow senses than to the runaway effects of the dynamic fusions of the by-products, not always hoped for, of two complex movements: The Protestant Reformation (and its bearings in respect of the newer orientations toward self, society, and the city of this world) and, The Scientific Revolution (and its consequences in the way of a development of an Universal symbolic mathematical science and technology). These fusions occurred at great heats toward the close of the 19th Century in Europe and the United States and are now at "the exponential growth point." Both of these movements began as fundamental critiques of the medieval integrated institutiion of "Conscience-Casuistry-and the Cure of Souls." In brief: The twofold changes in the fundamental "Moralities of Thought" and "Logics of Action" embraced in the earlier institution of conscience constitute the necessary foundations of the accelerated passage now in progress towards the universal automation of collective intelligence in the form of "Brain Machines" and "Memory Banks."